1976
DOI: 10.1128/aem.32.4.520-526.1976
|View full text |Cite
|
Sign up to set email alerts
|

Virus movement in soil columns flooded with secondary sewage effluent

Abstract: Secondary sewage effluent containing about 3 x 104 plaque-forming units of polio virus type 1 (LSc) per ml was passed through columns 250 cm in length packed with calcareous sand from an area in the Salt River bed used for groundwater recharge of secondary sewage effluent. Viruses were not detected in 1-ml samples extracted from the columns below the 160-cm level. However, viruses were detected in 5 of 43 100-ml samples of the column drainage water. Most of the viruses were adsorbed in the top 5 cm of soil. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 8 publications
5
35
0
2
Order By: Relevance
“…Dazzo et al (1973) found that only 10% of the fecal coliforms present in fresh dairy manure percolated below 13‐cm depth in soil; no coliforms were detected below a depth of 48 cm. Lance et al (1976) found that filtration through 250‐cm long columns filled with loamy sand reduced fecal coliform concentrations by about 3 logs during a 9‐d flooding period. Reneau et al (1975) concluded that soil layers restricted coliform bacteria movement to the groundwater system, and that the groundwater quality from the watershed would improve with distance from the pollution source as a result of dilution, sedimentation, and bacteria die‐off.…”
mentioning
confidence: 98%
“…Dazzo et al (1973) found that only 10% of the fecal coliforms present in fresh dairy manure percolated below 13‐cm depth in soil; no coliforms were detected below a depth of 48 cm. Lance et al (1976) found that filtration through 250‐cm long columns filled with loamy sand reduced fecal coliform concentrations by about 3 logs during a 9‐d flooding period. Reneau et al (1975) concluded that soil layers restricted coliform bacteria movement to the groundwater system, and that the groundwater quality from the watershed would improve with distance from the pollution source as a result of dilution, sedimentation, and bacteria die‐off.…”
mentioning
confidence: 98%
“…Rainwater, being of lower conductivity than sewage effluents, may thus lead to reduced viral and bacterial adsorption or to desorption with the subse quent redistribution of these organisms within the soil profile. This phenom enon was well demonstrated via soil core studies under controlled laboratory conditions [8,34,40,41]. Landry et al [43] showed that virus penetration was more extensive in rainwater-rinsed cores than in wastewater-rinsed cores.…”
Section: Saltsmentioning
confidence: 79%
“…At the lower infiltration rates, the surface mat of sewage solids that formed on the soil surface may have contributed to the greater virus removals observed. Lance et al [8] found that poliovirus type 1 removal was not affected by infiltration rates in the range of 15 to 55 cm per day. More recently Lance and Gerba [52] found that increasing flow rates from 0.6 to 1.2 m per day resulted in increased movement of viruses down the column.…”
Section: Infiltration Ratementioning
confidence: 99%
See 1 more Smart Citation
“…A filtração e a ação biológica de microrganismos, habitualmente presentes nos solos não estéreis, são os principais fatores de remoção microbiológica. A ação biológica é particularmente efetiva nas camadas superficiais do solo, onde a presença do ar facilita os processos aeróbios, mais intensivos do que os anaeróbios, e onde a disponibilidade maior de alimentos possibilita a existência de maior população de microrganismos (3,4). O outro fator determinante para uma eficaz ação biológica é o tempo.…”
Section: Introductionunclassified